Safety risks and ethical governance of biomedical applications of synthetic biology - Ou, Yakun; Guo, Shengjia (Frontiers in Bioengineering and Biotechnology, 2023)
Background: In recent years, biomedicine has witnessed rapid advancements in applying synthetic biology. While these advancements have brought numerous benefits to patients, they have also given rise to a series of safety concerns.This article provides a succinct overview of the current research on synthetic biology's application in biomedicine and systematically analyzes the safety risks associated with this field. Based on this analysis, the article proposes fundamental principles for addressing these issues and presents practical recommendations for ethical governance.Results: This article contends that the primary safety risks associated with the application of synthetic biology in biomedicine include participant safety, biosafety risks, and biosecurity risks. In order to effectively address these risks, it is essential to adhere to the principles of human-centeredness, nonmaleficence, sustainability, and reasonable risk control. Guided by these fundamental principles and taking into account China's specific circumstances, this article presents practical recommendations for ethical governance, which include strengthening ethical review, promoting the development and implementation of relevant policies, improving legal safeguards through top-level design, and enhancing technical capabilities for biocontainment.As an emerging field of scientific technology, synthetic biology presents numerous safety risks and challenges in its application within biomedicine. In order to address these risks and challenges, it is imperative that appropriate measures be implemented. From a Chinese perspective, the solutions we propose serve not only to advance the domestic development of synthetic biology but also to contribute to its global progress.